2016
DOI: 10.1002/ceas.12045
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American Women Pursuing Counselor Education Doctorates: A Narrative Inquiry

Abstract: The authors used narrative inquiry and Anzaldúa's () bordlerlands theory to understand the cultural experiences of 5 Mexican American women in doctoral programs accredited by the Council for Accreditation of Counseling and Related Educational Programs. Results indicated that participants navigated multiple cultural spheres and that the doctoral program culture affected their professional identity. Implications for counselor education include engaging Mexican American women in academic activities congruent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 16 publications
4
47
0
Order By: Relevance
“…Narrative research draws upon a wide range of oral and autobiographical storytelling from around the globe, which transcend national and cultural boundaries and provides a route for understanding diverse lives (Chinyamurindi, 2016;Coetzee & Nuttall, 1998;Cortazzi & Jin, 2006;Hinojosa & Carney, 2016;Lessard, Caine & Clandinin, 2015;Trahar, 2006). Located within this field is a small, but growing number, of researchers who are adopting a more multimodal and multisensory approach by focusing upon embodied, active or emotional engagements that occur during storytelling.…”
Section: Framing Life History Narrative Researchmentioning
confidence: 99%
“…Narrative research draws upon a wide range of oral and autobiographical storytelling from around the globe, which transcend national and cultural boundaries and provides a route for understanding diverse lives (Chinyamurindi, 2016;Coetzee & Nuttall, 1998;Cortazzi & Jin, 2006;Hinojosa & Carney, 2016;Lessard, Caine & Clandinin, 2015;Trahar, 2006). Located within this field is a small, but growing number, of researchers who are adopting a more multimodal and multisensory approach by focusing upon embodied, active or emotional engagements that occur during storytelling.…”
Section: Framing Life History Narrative Researchmentioning
confidence: 99%
“…Espino's study suggests that these Mexican American women found a sense of empowerment as they learned to successfully integrate both the conflicting and supportive consejos and find ways to excel in academia. Studies also suggest that when Latina women PSEs are able to integrate their cultural identities into their professional identities (e.g., teach about culturally relevant topics, research issues related to their cultures), they feel empowered (Castillo-Montoya & Torres-Guzmán, 2012;Hinojosa & Carney, 2016). Conversely, research suggests that Latinas in post-secondary settings feel disempowered when they are silenced or neglected.…”
Section: Empowerment/disempowermentmentioning
confidence: 99%
“…However, we noticed that these three concepts incorporated contrasting characteristics. For example, studies indicate that Mexican American women often use their voice, or sense of agency, to stand up for themselves within post-secondary education settings, but also often feel their voices are silenced, or ignored, in these same environments (Hinojosa & Carney, 2016).…”
Section: Professional Development Of Women Of Colormentioning
confidence: 99%
See 2 more Smart Citations